ナンキョク ノ エンコ ノ ドウイタイ チキュウ カガクテキ ケンキュウ - 松葉谷, 治; マツバヤ, オサム; 酒井, 均; サカイ, ヒトシ; 鳥居, 鉄也; トリイ, テツヤ; MATSUBAYA, Osamu; SAKAI, Hitoshi; TORII, Tetsuya (国立極地研究所, 1977)
P(論文) 南ビクトリアランド,宗谷海岸,およびベストホールド・ヒルズの塩湖の成因を明らかにする目的で,湖水の水素および酸素同位体比を測定した.これらの水素および酸素同位体比の関係は天水の関係よりも^<18>Oを濃縮する方向にずれており,氷河融水の湖への流入量が湖からの蒸発量と釣り合っており,その蒸発のさいの同位体効果により,湖水の同位体比が規制されていることを示している.南ビクトリアランドのボニー湖とバンダ湖では,淡水層と塩水層の混合に関する拡散モデルにより,氷河融水が流入し姶めた時期は,ボニー西湖が5,800年前,ボニー東湖が1,500年前,バンダ湖が1,200年前と推定される.これらの塩湖の塩類は,Na^+/Mg^<2+>あるいはCl^-/Br^-比とCl^-濃度の関係より,海水起源と考えられるが,バンダ湖およびドンファン池は他と異なり,直接海水を起源とするとは考えにくい. In order to understand the origin of saline lakes in the southern Victoria Land, Soya Coast, and Vestfold Hills, the hydrogen and oxygen isotopic ratios of lake waters were measured. The relationship between the two isotopic ratios in these lakes shifted from that of meteoric water in the direction of enrichment in ^<18>O. This suggests that these lakes are in steady state balance with respect to mass and isotopic ratios between melt-water input and kinetic evaporation. In the southern Victoria Land, it is estimated that the inflow of melt water from glaciers might have begun at 5,800 years ago in the west lobe of Lake Bonney, 1,500 years ago in the east lobe of Lake Bonney, and 1,200 years ago in the Lake Vanda, respectively, on the basis of diffusion model for the mixing between the saline layer and the fresh water layer. The relationship of Na^+/Mg^<2+> and Cl^-/Br^- to Cl^- content indicates that the salts in these lakes might have come from sea water, except for Lake Vanda and Don Juan Pond the compositions of which cannot be explained by the direct sea water origin. departmental bulletin paper